Qolqa: A Metrics-Driven Design Tool for Document-Oriented NoSQL Databases - Alagon-Fernandez, Anghelo; Chirinos-Vilca, Yerson Joab; Holanda, Maristela; Vera-Olivera, Harley (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD); 2026: Anais Estendidos do XLI Simpósio Brasileiro de Bancos de Dados, 2026)
Document-oriented NoSQL databases, although considered schema-less, require design tools to understand the structural context of schemas, including document organization, attributes, and nesting levels. However, current tools present limitations as they rely heavily on the designer’s experience, lack metrics to evaluate schema quality, and do not integrate queries as part of the design process. Additionally, many of these solutions are commercial or have restricted free versions, which hinders the development of optimal solutions. In this context, this work proposes Qolqa, a web-based tool for designing schemas in document-oriented NoSQL databases that incorporates evaluation metrics, integrates queries as a relevant component of the design, and supports multiple schemas within a single solution. The proposed approach aims to facilitate decision-making in schema design and improve the quality of solutions, regardless of the designer’s level of experience.